Can large doses of glucocorticoids lead to Perthes? a case report and review of the literature - Guoming Chen (BMC Pediatrics, 2021)
Abstract Background Perthes disease (Legg-Calvé-Perthes, LCP) is a self-limited and non-systemic disease occurring in the femoral heads of children, which is mainly manifested as an ischemic necrosis of the femoral head epiphysis, leading to subchondral ossification injury of the femoral head. Case presentation Here we report a case of 11-year-old child with long-term use of high-dose glucocorticoids. With MRI examination finding the epiphyseal necrosis of right humeral head, femur and tibia, and X-ray examination finding bilateral femoral head necrosis, the child was diagnosed as Perthes disease based on his clinical and imaging data. Conclusions Long-term and high-dose glucocorticoids may be one of the causes of Perthes disease.